What is the answer? `9 - 5 + 5* 0 + 3 =`  I say the answer is 12, want to be sure I'm right. Other people say: 7. How is that?  

Expert Answers
lemjay eNotes educator| Certified Educator

`9-5+5*0+3`

To simplify, apply the order of operations known as PEMDAS (Parenthesis, Exponent, Multiplication/Division, and Addition/Subtraction.

Note that the operations involved in the given expression are subtraction, addition and multiplication.

So multiply first 5 and 0, since in PEMDAS, multiplication comes before addition and subtraction.

`=9-5+0+3`

Then, moving from left to right in the resulting expression, do the subtraction.

`=4+0+3`

And, do the addition.

`=7`

Hence, `9-5+5*0+3=7` .